New opportunities for allergen immunotherapy using synthetic peptide immuno-regulatory epitopes (SPIREs) - Klimek, Ludger; Pfaar, Oliver; Worm, Margitta (Expert review of clinical immunology, 2016)
Introduction: Allergen immunotherapy (AIT) reduces allergic rhinoconjunctivitis (ARC) symptoms, but long-term efficacy requires treatment for 3-5 years. Synthetic peptide immuno-regulatory epitopes, a new class of AIT, are allergen peptides with a shorter, more convenient treatment regimen that could potentially have benefits on adherence and outcomes.Areas covered: Phase 2 trials of therapies derived from cat, house dust mite, grass, and ragweed allergen peptides demonstrated significant reduction in ARC symptoms after short-course treatment; improvement was sustained for 18-24 months posttreatment. We conducted a PubMed literature search for clinical publications using the search terms AIT; allergen peptides; ARC; cat, grass, house dust mite, and ragweed allergy; SCIT; SLIT; and synthetic peptides.Expert commentary: Long-term disease modification is a realistic goal of AIT. The inconvenience of conventional AIT regimens negatively impacts long-term persistence and, thus, efficacy. In comparison, SPIREs have a more convenient treatment regimen that could potentially have benefits on adherence and outcomes.